RED-100 detector for the first observation of the elastic coherent neutrino scattering off xenon nuclei. Issue 1 (January 2016) - Akimov, D Yu; Berdnikova, A K; Belov, V A; Bolozdynya, A I; Burenkov, A A; Efremenko, Yu V; Gusakov, Yu V; Etenko, A V; Kaplin, V A; Khromov, A V; Konovalov, A M; Kovalenko, A G; et al.
Abstract: The RED-100 (Russian Emission Detector) is being constructed for the experiment to search for elastic coherent neutrino scattering off atomic nuclei. This fundamental process was predicted several decades ago by the Standard Model of electroweak interactions but has not been discovered yet. The RED-100 is a two-phase emission xenon detector containing ∼200 kg of the liquid Xe (∼ 100 kg of that is in a fiducial volume). One of the possible sites to carry out the experiment is the SNS (Spallation Neutron Source) facility at Oak Ridge National Laboratory, USA. SNS is the world's most intense pulsed source of neutrinos and unique place to study neutrino properties. The energy spectrum of neutrinos produced at the SNS extends up to ∼ 50 MeV and satisfies coherence condition. These neutrinos give kinetic energies of Xe recoils up to a few tens of keV where the response of nuclear recoils is well-known from neutron calibrations of dark matter detectors. The detector will be deployed in the basement under the experimental hall at a distance of ∼30 meters from the SNS target. The expected signal and background (neutron and gamma) are estimated for this specific location. The detector details, current status and future plans are provided.